Proceedings of the 4th ACM/IEEE-CS Joint Conference on Digital Libraries 2004
DOI: 10.1145/996350.996433
|View full text |Cite
|
Sign up to set email alerts
|

Supporting personal collections across digital libraries in spatial hypertext

Abstract: Creating, maintaining, or using a digital library requires the manipulation of digital documents. Information workspaces provide a visual representation allowing users to collect, organize, annotate, and author information. The Visual Knowledge Builder (VKB) helps users access, collect, annotate, and combine materials from digital libraries and other sources into a personal information workspace. VKB has been enhanced to include direct search interfaces for NSDL and Google. Users create a visualization of sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Alternatively would more note-taking in fact indicate that reading is being interrupted and users are calling more on notes to support a reading task that has been made more complex? In order to obtain a principled model for our study, we have drawn strongly upon Shipman's analysis of VKB [24] who faced similar problems: the correct interpretation of artefacts and metrics for the task was imperfectly understood.…”
Section: Study Metricsmentioning
confidence: 99%
“…Alternatively would more note-taking in fact indicate that reading is being interrupted and users are calling more on notes to support a reading task that has been made more complex? In order to obtain a principled model for our study, we have drawn strongly upon Shipman's analysis of VKB [24] who faced similar problems: the correct interpretation of artefacts and metrics for the task was imperfectly understood.…”
Section: Study Metricsmentioning
confidence: 99%
“…Web document object with two object layers uses the system layer's visual attributes to provide cues, hints, or suggestions without interfering with user expression. We developed this extension in response to previous study results that suggested users were reluctant to express their own interpretations once the system had applied its own visualizations to objects [28]. Figure 3 illustrates a triage scenario.…”
Section: Vkb 3: System Enhancementsmentioning
confidence: 99%
“…Prior versions of VKB are described in detail in [26][27] [28]. The application is written in JAVA and runs on MS Windows, Apple's OS X, and Linux.…”
Section: Vkb 3: System Enhancementsmentioning
confidence: 99%
“…Prior versions of VKB are described in detail in [26][27] [28]. The application is written in JAVA and runs on MS Windows, Apple's OS X, and Linux and VKB 2 is available for download at http://www.csdl.tamu.edu/VKB.…”
Section: Visual Knowledge Buildermentioning
confidence: 99%